Common infectious diseases and skin test anergy in children from an urban slum in Northeast Brazil - Melânia X. Castro; Alberto M. Soares; Walter Fonsêca; Luís C. Rey; Richard L. Guerrant; Aldo A. M. Lima (Brazilian Journal of Infectious Diseases)
BACKGROUND: Acute respiratory infection (ARI), diarrheal disease (DD) and infective dermatitis (ID) are important causes of morbidity in children under five, in Northeast Brazil. Objectives: (a) to evaluate the morbidity of ARI, DD and ID; and (b) to determine their association with cellular immunity in poor urban children from Fortaleza, Brazil. MATERIALS AND METHODS: A prospective cohort study. At enrollment, multipuncture skin-tests (Multitest CMI) were performed and interpreted according to standard procedures. Children were followed for infectious diseases by weekly home visits. RESULTS: Seventy-one children aged 6 to 21 months were recruited in an ongoing cohort of newborns. A mean of 39 (6 to 63) home visits per child were made, which detected 184.5 symptomatic days per child-year of observation. ARI was present in 62% of the days of illness (6,378 out of 10,221), DD in 23% (2,296 days), ID in 6% (597) and other infections in 4% (373). Episodes per child-year were: 10 for ARI, 7 for DD and 1 for ID. Twelve (17%) out of 71 children were anergic. The incidences of ARI, DD and ID were similar in responsive versus anergic children. The mean duration of ID in anergy was 8.5 days, while it was 4.3 in the responsive group (P=0.007). Anergy was independent of age, sex and nutritional status. CONCLUSIONS: A high incidence of ARI and DD was found in these poor urban children. Skin-test responsiveness was not related to malnutrition, nor to morbidity due to ARI and DD, however anergic children had a longer duration of infective dermatitis.